2017
DOI: 10.3892/ol.2017.7218
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Beclin 1 and Bcl‑2 in pancreatic neoplasms and its effect on pancreatic ductal adenocarcinoma prognosis

Abstract: Aberrant expression of Beclin 1 and B-cell lymphoma-2 (Bcl-2) has been identified in a variety of human tumors; however, little information is available for pancreatic neoplasms. The present study analyzed the expression of Beclin 1 and Bcl-2 in pancreatic ductal adenocarcinoma (PDAC) and solid pseudopapillary neoplasm (SPN) of the pancreas, and evaluated their prognostic significance for PDAC. The present study included 117 PDAC, 43 SPN and 32 chronic pancreatitis (CP) cases. Levels of Beclin 1 and Bcl-2 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…Postoperative pathology confirmed the result of preoperative imaging diagnosis. Immunophenotyping showed synaptophysin (+), CD56(+), CD10(+), β-catenin(+), vimentin (+), and AE1/AE3(+), which met the diagnostic criteria for SPTP, and was consistent with the histopathological diversity of SPTP[12-14]. Vimentin, β-catenin, synaptophysin, neuron-specific enolase, α1-antitrypsin (α1-AT), S-100, neural cell adhesion molecule CD56, and cluster of differentiation 10 (CD10) can all be expressed in SPTP[15-17].…”
Section: Discussionmentioning
confidence: 84%
“…Postoperative pathology confirmed the result of preoperative imaging diagnosis. Immunophenotyping showed synaptophysin (+), CD56(+), CD10(+), β-catenin(+), vimentin (+), and AE1/AE3(+), which met the diagnostic criteria for SPTP, and was consistent with the histopathological diversity of SPTP[12-14]. Vimentin, β-catenin, synaptophysin, neuron-specific enolase, α1-antitrypsin (α1-AT), S-100, neural cell adhesion molecule CD56, and cluster of differentiation 10 (CD10) can all be expressed in SPTP[15-17].…”
Section: Discussionmentioning
confidence: 84%
“…Upregulated SMAD3 promotes epithelial mesenchymal transition and predicts poor PDAC [60,61]. Also, it has been reported that BCL2 downregulated expression is a poor prognostic factor for PDAC [62]. TGF-β1 levels are significantly related to PDAC patients’ prognosis [63].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has indicated that in breast cancer Beclin-1 may serve a role in the inhibition of the development of breast cancer, which may be due to an interaction with the Bcl-2 protein (30). In pancreatic cancer, a study by Shanshan et al (10) demonstrated that high Bcl-2 and low Beclin-1 expression was associated with an improved DFS and OS. The present study further evaluated the expression levels of Beclin-1 in NSCLC tissue specimens with different expression levels of Bcl-2 via immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…However, the binding of Bcl-2 to Beclin-1 is regulated by a variety of proteins, which enhance or inhibit the Beclin-1/Bcl-2 interaction and further inhibiting or activating autophagy and apoptosis, thus the Beclin-1/Bcl-2 complex act as a crosstalk between autophagy and apoptosis (9). Previous studies have demonstrated that the expression levels of Beclin1 and Bcl-2 in tumor cells depend on the tumor and tissue type (10)(11)(12); however, this requires further investigation.…”
Section: Introductionmentioning
confidence: 99%